Metasurface-enabled three-in-one nanoprints by multifunctional manipulations of light - Zile Li; Liangui Deng; Juan Deng; Zhixue He; Jin Tao; Guoxing Zheng; Shaohua Yu (iScience, 2021)
Summary: In metasurface-based ultra-compact image display, color-nanoprints, gray-imaging elements, and binary-pattern-imaging elements are three different types of nanoprints, implemented with different mechanisms of light manipulation. Here, we show the three functional elements can be integrated together to form a “three-in-one” nanoprint with negligible crosstalk, merely with a single-cell nanostructured design approach. Specifically, by decoupling spectrum and polarization-assisted intensity manipulations of incident light, the proposed metasurface appears as a dual-color nanoprint under a broadband unpolarized light source illumination, while simultaneously displaying an independent continuous gray image and another binary-pattern in an orthogonal-polarization optical setup with different polarization controls. Our approach can increase the system integration and security of metasurfaces, which can be of interest to many advanced applications such as data storage, optical information encoding, high-end optical anti-counterfeiting, and optical information hiding.